A Study on the Relationship between Management Accounting Practices, Strategy Alignment and Organizational Performance - Lee, Mei Yi (2014)
Organizations have widely adopted cost leadership and differentiation strategy to remain competitive in today’s business environment. Roles of management accountants have changed over the past decades from technical towards strategic competence to support business development while management accounting practices have been widely adopted to satisfy the information needs of business in the current pace of competitive business environment. The research objective is to investigate the influence of degree of fit on the relationship between competitive strategies, management accounting practices and organizational performance and to examine the moderating effect of management accounting practices on the strategy-performance relationship. This is a descriptive research using quantitative research methodology by investigating 132 respondents who are the registered members from the professional body of Chartered Institute of Management Accountants (CIMA). Descriptive analysis of respondents, adoption rate of management accounting practices and ranking of strategic priorities were analyzed using IBM SPSS. Validity and reliability of the measurement model and assessment of structural model were analyzed by PLS-SEM. Multiple association between management accounting practices, competitive strategy and organizational performance. Results indicated that both cost leadership and differentiation strategy that are supported respectively by traditional and contemporary management accounting practices will have higher correlation with the organizational performance. It is concluded that organization that plans to adopt a cost leadership strategy or differentiation strategy to dominate the market need to emphasize on traditional and contemporary management accounting practices respectively to achieve greater performance.